Ensuring the operational efficiency of mining and metallurgical enterprises on the basis of sustainable development - Латишева, О. В.; Ровенська, В. В.; Смирнова, І. І.; Тріпак, М. М.; Теплюк, М. А.; Latysheva, O. V.; Rovenska, V. V.; Smyrnova, I. I.; Tripak, M. M.; Tepliuk, M. A. (Національний гірничий університет, 2024)
Purpose. To improve dynamic management of operational efficiency (DMOE) to ensure the sustainable development (SD) of the enterprise in the conditions of challenges. The task of the article is: to investigate external influences on the functioning of min ing and metallurgical enterprises (MME); to identify prerequisites for DMOE, directions for improvement of operational effi ciency of management tools

Мета. Вдосконалення динамічного управління операційною ефективністю для забезпечення сталого розвитку підприємства в умовах сучасних викликів. Завдання роботи: дослідити зовнішні впливи на функціонування гірничих і металургійних підприємств; виявити передумови динамічного управління операційною ефективністю, напрями вдосконалення інструментів управління операційною ефективністю.
Забезпечення операційної ефективності гірничого-металургійних підприємств на засадах сталого розвитку
Keywords: sustainable development; operational efficiency; mining and metallurgical enterprises; сталий розвиток; операційна ефективність; гірничо-металургійне підприємств